Infections following Immediate Implant-Based Breast Reconstruction: A Case-Control Study over 11 Years. Issue 6 (December 2019) - Banuelos, Joseph; Sabbagh, M. Diya; Roh, Si-Gyun; Nguyen, Minh-Doan T.; Lemaine, Valerie; Tran, Nho V.; Jacobson, Steven R.; Boughey, Judy C.; Jakub, James W.; Hieken, Tina J.; Degnim, Amy C.; Mandrekar, Jay; et al.
Abstract : Background: Surgical-site infection after implant-based breast reconstruction adversely affects surgical outcomes and increases health care costs. This 11-year case-control study examines risk factors specific for surgical-site infection after immediate tissue expander/implant-based breast reconstruction. Methods: The authors performed a retrospective review to identify all consecutive patients with breast implant infections between 2006 and 2016. Patients who developed surgical-site infection after immediate tissue expander/implant-based breast reconstruction were included. Surgical-site infection was defined using the Centers for Disease Control and Prevention criteria; specifically, infections requiring hospital admission, intravenous antibiotics, or surgical intervention were included. The authors matched a control patient to each infection case by patient age and date of surgery. Patient demographics, medical comorbidities, and perioperative surgical variables were examined. Univariate and multivariable conditional logistic regression models were constructed. Results: A total of 270 breasts in 252 patients were evaluated. On multivariate analysis, patients with a higher body mass index (OR, 1.1 per 1 body mass index point increase; 95 percent CI, 1.0 to 1.2; p = 0.02), hypertension (OR, 6.5; 95 percent CI, 1.9 to 22.3; p = 0.002), neoadjuvant chemotherapy (OR, 2.6; 95 percent CI, 1.0 to 6.3; p = 0.04), axillary lymph node dissection (OR, 7.1; 95 percent CI, 1.7 to 29.2; p = 0.006), seroma formation (OR, 15.34; 95 percent CI, 3.7 to 62.5; p = 0.0001), and wound healing complications (OR, 23.91; 95 percent CI, 6.1 to 93.4; p < 0.0001) were significantly associated with surgical-site infection. Conclusions: Women with obesity, women with hypertension, and those treated with neoadjuvant chemotherapy are at increased risk of surgical-site infection. Further risks are also associated with postoperative seroma and wound complications. This may help patient selection and counseling, adjusted based on risk factors regarding complications of immediate implant-based breast reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.